View Single Post
Old
01-28-2013, 10:59 PM
  #370
18Hossa
Registered User
 
18Hossa's Avatar
 
Join Date: Oct 2012
Posts: 4,686
vCash: 50
Quote:
Originally Posted by Deku Scrub View Post
I'm unsure about converting standard form to y=mx+b. I think I know how to do it but I'm not sure.
Let's see if I can help

Say the equation is 6x-3y+12=0 then you would change it to -3y=-6x-12 then after that you would have to divide -6x and 12 by -3 giving you y=-2x+4

tl;dr
6x-3y+12=0
-3y=-6x-12
y=-2x+4

Hope that helps :


Last edited by 18Hossa: 01-28-2013 at 11:05 PM.
18Hossa is online now